Financial Education for the Elderly in a Low-Income Context - Caroline Stumpf Buaes (Universidade Federal do Rio Grande do Sul, 2014)
This article discusses consumption among Brazilian low-income elderly people and the importance of considering educational interventions designed for this population. The discussion stems from a participant observation research, developed by means of a pedagogical action performed with elderly women, founded on popular educational principles and cultural-historical approach. Results showed that the participants collectively produced financial control strategies and new conceptual constructions of consigned credit mechanisms. Lastly, some principles advocate the generation of educational practices that promote empowering and protagonism among elderly consumers.